2003
DOI: 10.1111/1536-7150.00216
|View full text |Cite
|
Sign up to set email alerts
|

Variations in NHL Attendance: The Impact of Violence, Scoring, and Regional Rivalries

Abstract: In recent years the National Hockey League (NHL) has put policies in place to boost attendance. Specifically, these changes have been to curb violence, increase scoring, and move to an unbalanced schedule featuring more games against regional rivals. This research looks at variations in game‐to‐game attendance in the NHL, focusing on these policy changes. It is found that violence, specifically fighting, tends to attract fans in large numbers across the United States and Canada. Surprisingly, increases in scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 3 publications
(7 reference statements)
1
41
0
Order By: Relevance
“…Accordingly, many authors have found that opening games of the season attract higher attendances. Paul (2003) observed that opening night home games in the NHL (but not the subsequent matches at the beginning of the season) had more spectators. Suominen (2009) found that as the Finnish ice hockey season progressed, the attendances decreased.…”
Section: Team Freshness/newnessmentioning
confidence: 95%
See 4 more Smart Citations
“…Accordingly, many authors have found that opening games of the season attract higher attendances. Paul (2003) observed that opening night home games in the NHL (but not the subsequent matches at the beginning of the season) had more spectators. Suominen (2009) found that as the Finnish ice hockey season progressed, the attendances decreased.…”
Section: Team Freshness/newnessmentioning
confidence: 95%
“… Another budget-related approach to assessing English soccer team quality was employed by Buraimo (2008), who used the team's wage bill divided by the respective division's average wage bill in the season.  T o measure short-term quality, it is common to use the number of points per match in the current season -this approach was utilized by, for example, Borland and Lye (1982) for Australian Rules football, 54 Welki and Zlatoper (1994) for US football, Forrest and Simmons (2002) for English soccer, Paul (2003) for NHL, and Suominen (2009) for Finnish ice hockey. The problem of this approach is that this indicator is unavailable for the first matches of the season -one possible, albeit problematic, 55 solution is to leave the first matches out.…”
Section: Team Quality/reputationmentioning
confidence: 99%
See 3 more Smart Citations